Financial Analysis of Bamboo Based Agroforestry Models - Ashutosh, S.; Vishwakarma, Paresh; Nema, Sharad (Indian Forester, 1996)
Financial profitability and economic returns from Agroforesty practices of bamboo cultivation has been discussed in this pappr.